Impact of Ovarian Cyst Size on Pregnancy Course and Neonatal Outcomes: Does Size Really Matter? - Duygulu Bulan, Dilara; Dayanan, Ruken; Ayas Ozkan, Merve; Aksoy, Rıfat Taner; Çağlar, Ali Turhan (The European Research Journal, 2026)
Objectives: This study aimed to evaluate the impact of benign ovarian cyst size on maternal and neonatal outcomes by comparing pregnancies complicated by cysts of different diameters. Methods: In this retrospective cohort study, 266 pregnant women diagnosed with benign ovarian cysts were categorized into three groups according to cyst diameter: 10 cm. Maternal characteristics, pregnancy complications, delivery outcomes, and neonatal parameters were analyzed. Composite adverse perinatal outcomes (CAPO) included prematurity, low Apgar scores, neonatal intensive care unit (NICU) admission, and neonatal morbidities. Results: Most small cysts (10 cm were associated with increased risks of preterm delivery (23.1%), composite adverse perinatal outcomes (26.9%), and higher incidences of torsion, rupture, and surgical intervention (P10 cm carry a markedly higher likelihood of maternal complications and adverse perinatal outcomes, supporting closer surveillance and individualized, size-based management strategies.